Ultrasound-Guided Superficial Cervical Plexus Block for Anterior Cervical Discectomy and Fusion in a Patient with Herniated Nucleus Pulposus: A Case Report - Elanda Rahmat Arifyanto; Aura Ihsaniar (HM Publisher, 2025)
Anterior cervical discectomy and fusion (ACDF) is a surgical procedure performed to alleviate pressure on the spinal cord and nerve roots in the neck. Effective pain management is crucial for optimal postoperative recovery. Superficial cervical plexus block (SCPB) has emerged as a safe and effective regional anesthesia technique for head and neck surgeries. This case report describes the successful use of ultrasound-guided SCPB for ACDF in a patient with a herniated nucleus pulposus. In this study, a 48-year-old male patient presented with lower extremity weakness and hypoesthesia following a fall. Magnetic resonance imaging (MRI) revealed a herniated nucleus pulposus at the C5-6 level. The patient underwent ACDF surgery under ultrasound-guided SCPB. Levobupivacaine 0.5% 10 cc was administered bilaterally. The patient tolerated the procedure well, with no complications or adverse events. Postoperative pain was effectively managed with SCPB, and the patient's neurological symptoms improved significantly. In conclusion, ultrasound-guided SCPB is a safe and effective anesthetic technique for ACDF surgery in patients with herniated nucleus pulposus. It provides adequate pain control, reduces opioid requirements, and facilitates early mobilization and recovery.